Transparent Epidermal Antenna for Unobtrusive Human-Centric Internet of Things Applications - Simorangkir, Roy B. V. B.; Gawade, Dinesh R.; Hannon, Tim; Donovan, Paul; Kumar, Sanjeev; Rather, Nadeem; Moloudian, Gholamhosein; O'Flynn, Brendan; Buckley, John L. (IEEE internet of things journal, 2024)
The concept of optical transparency in antennas for epidermal electronics is demonstrated in this work as a means of improving the long-term comfort-of-wear level and possibly opening up a wider range of applications. In contrast to previous attempts, the epidermal antenna transparency is achieved by employing dielectric and conductive materials that are both transparent and flexible (i.e., polydimethylsiloxane-transparent conductive textile composite) via a non-clean room procedure that is relatively simpler and less expensive. To demonstrate the concept, a modified rectangular loop epidermal antenna for an arm-worn wireless sensing system operating at 868 MHz Ultra High Frequency (UHF) band is designed. Through a systematic numerical investigation, an interesting radiation response of the loop epidermal antenna as the result of two opposing mechanisms of radiation and loss is revealed, which dictates a specific design guideline for the loop when attached to the body compared to that in free space. Two antenna prototypes were fabricated with the developed transparent composite and its non-transparent counterpart. Then, comprehensive characterizations comparing both epidermal antenna prototypes were carried out, including antenna return loss and far-field tests on a human forearm phantom, and indoor wireless connectivity tests using a human test subject. By showing similar performance between the two prototypes, the study provides a convincing demonstration of the applicability of the developed transparent composite for the class of epidermal antenna and the capability of a transparent antenna to enable wireless connectivity in the context of epidermal electronics.